Analysis of Acquisition and Titer of Maize Mosaic Rhabdovirus in Its Vector, Peregrinus maidis (Hemiptera: Delphacidae). Issue 1 (5th February 2016) - Barandoc-Alviar, Karen; Ramirez, Girly M.; Rotenberg, Dorith; Whitfield, Anna E.
Abstract: The corn planthopper, Peregrinus maidis (Ashmead) (Hemiptera: Delphacidae), transmits Maize mosaic rhabdovirus (MMV), an important pathogen of maize and sorghum, in a persistent propagative manner. To better understand the vectorial capacity of P. maidis, we determined the efficiency of MMV acquisition by nymphal and adult stages, and characterized MMV titer through development. Acquisition efficiency, i.e., proportion of insects that acquired the virus, was determined by reverse transcriptase polymerase chain reaction (RT-PCR) and virus titer of individual insects was estimated by quantitative RT-PCR. Acquisition efficiency of MMV differed significantly between nymphs and adults. MMV titer increased significantly over time and throughout insect development from nymphal to adult stage, indication of virus replication in the vector during development. There was a positive association between the vector developmental stage and virus titer. Also, the average titer in male insects was threefold higher than female titers, and this difference persisted up to 30 d post adult eclosion. Overall, our findings indicate that nymphs are more efficient than adults at acquiring MMV and virus accumulated in the vector over the course of nymphal development. Furthermore, sustained infection over the lifespan of P. maidis indicates a potentially high capacity of this vector to transmit MMV.